Economic burden of meningococcal disease in children and adolescents in Tijuana, Mexico - Enrique Chacon-Cruz; Erika Zoe Lopatynsky-Reyes; Gloria Huerta-Garcia; Maria Yolanda Cervantes-Apolinar; Adriana Guzman-Holst; Desiree Van Oorschot (Taylor & Francis Group, 2022)
Invasive meningococcal disease (IMD) is an uncommon but serious and potentially fatal condition mainly affecting children and adolescents. Active surveillance between 2005 and 2016 at Tijuana General Hospital, Mexico, indicated that the incidence of IMD in Tijuana was higher than previously thought, at 2.69 per 100,000 population aged <16 years. The objective of this study was to estimate the economic burden associated with 51 IMD cases in children aged <16 years identified over the 11 years of active surveillance at Tijuana General Hospital, Mexico. Healthcare resource usage for the IMD cases was obtained from the hospital database and combined with unit costs from the hospital purchasing department or national databases to estimate total healthcare costs over a follow-up period of 3 months. Societal costs were represented by the value of lost wages for parents or guardians. All costs were expressed in US$. Over the 11-year study period there were 51 IMD cases, of which 13 (25%) were fatal. The total cost for all 51 cases over the 11-year study period was US$1,054,499 (average per case US$20,676), of which direct healthcare costs comprised US$1,029,948 (average per case US$20,195) and societal costs US$24,551 (average per case US$481). Extrapolated to the population of Tijuana region aged <16 years, the estimated annual economic burden of IMD was US$268,794. The major cost driver was the cost of hospitalization. These data illustrate the significant economic burden associated with IMD in Tijuana, and will be useful in assessing optimal vaccination programs against meningococcal disease in Mexico.